Representação do gênero Mactra Linnaeus, 1767 no Estado do Rio de Janeiro, Brasil (Mollusca, Bivalvia, Mactridae) - Brandão, Antonio Marmo (1982)
The main objective of this essay is the study of marine bivalves mollusks of the genus Mactra Linnaeus, 1767, which belongs to the Mactridae family, found in the coastal area of the state of Rio de Janeiro. The characteristics from subclass to subgenus are presented in this study. Besides, there are discussions related to taxonomics, morphologics and ecologics characteristics Connected with geological and geographical distribuitions for the following species: Mactra (Mactra) isabelleana Orbigny, Mactra (Mactra) patagonia Orbigny, Mactra (Mactra) marplatensis Doello - Jurado, Mactra (Micromactra) Janeiroensis Smith, Mactra (Mactrotoma) petiti Orbigny e Mactra (Mactrotoma) fragilis: Gmelin.